Perempuan Desainer Berdikari dalam Industri Kreatif di Indonesia - Senja Aprela Agustin; Acep Iwan Saidi; Irma Damajanti (Universitas Persada Indonesia YAI, 2023)
This paper depicts the work of three women designers in the informal sector of the creativeindustry in Indonesia. The unique works of women designers in designing and building brands oflocal-domestic products, fashion, decorations, and, accessories produced in home-based studioshave made them financially self-sustaining. In addition, this research also shows that the ability ofwomen designers to negotiate in society which still burdens women with domestic activities can beself-supported and develop their businesses. Furthermore, the factors that influence the success ofbusiness sustainability include: 'personal style' design, ability to understand the market,proficiency in computer technology, and the utilization of communication media such as socialmedia and websites. This independent women designer figure in the informal sector indirectlycontributes to economic prosperity in Indonesia